Burden on Family Caregivers of Children with Autism Spectrum Disorder: A Cross-Sectional Study - Barik, Smitabh; Pattanaik, Sumitra; Patnaik, Lipilekha; Sarangi, Rachita (National Journal of Community Medicine, 2025)
Background: Children with Autism spectrum disorders need special care and understanding. This study aimed to assess burden and challenges faced by caregivers of children with ASD aged 2-10 years in Bhubaneswar, Odisha. Materials and methods: A cross-sectional study conducted in Bhubaneswar, Odisha over two and half years. Data were collected from 12 autism therapy centres and schools. Caregiver Strain Questionnaire (CGSQ) with socio-demographic details of caregivers was used for assessment of challenges and experiences of caregivers. Results: The mean age of mothers was 34.74 ± 3.40 years and the mean age of fathers was 40.02 ± 3.65 years. Highest level of strain as reported by caregivers was on subjective internalized subscale i.e. 3.07 ± 0.39 followed by objective strain subscale with mean score of 2.29 ± 0.46. Education, socio-economic status and family type were significantly associated with CGSQ score (P<0.05). Caregivers of children with autism spectrum disorder have significantly higher strain in low education levels, lower middle socio-economic status and nuclear families. Conclusion: Caregivers experience a lot of challenges in parenting the child with ASD, so more educational and counselling sessions are needed to decrease their stress and improve the quality of life.